Rheology characterization of a solder paste - Barbosa, Flávia Vieira (2018)
Reflow soldering process is widely implemented in the electronics industry. This method allows the attachment of electronic components to a printed circuit board (PCB) through the melting of solder paste, which makes the interconnection between them. The reflow soldering process must ensures the correctly melting of the solder paste and heating of the adjoining surfaces, without the electronic components suffer overheating or any other type of damage. Solder paste is the most widespread material in the SMT (Surface Mount Technology) process using reflow soldering. An ideal solder paste will increase production efficiency, decreasing the amount of defects associated with the reflow soldering process. However, several factors affects the performance of the solder paste, from rheology, printability, and reliability to the adhesion strength of components and the ability to avoid defects related to reflow. Therefore, all these factors need to be considered during the selection of a solder paste for a specific application. The rheological properties were determined using both a double cylinder (PHYSICA-RHEOLAB MC1) and a double plate (Malvern) rheometers. The later enable the determination of viscoelastic properties. The present paper analyses the rheological behavior of a SAC405 solder paste, a mixture containing a metal alloy powder (25-45 μm) and a flux which at its base is a resin. The tests were carried out at conditions (temperature and shear rate) of relevance to the printing process. The results obtained show that the paste viscosity closely follows the Herschel-Bulkley model and shows a thixotropic behavior without fully recovery between applications. In addition, the viscosity decreases with the increase of shear rate confirming that the solder paste is a non-Newtonian fluid, shear thinning in behavior. The oscillatory tests have shown that the transition from elastic to viscous behavior occurs at a shear stress above 35 Pa. On the other hand, the creep/recovery test confirms that the level of solicitation influences the capacity of recovery of the solder paste.